Metabolomics and pharmacogenetics based 5-fluorouracil monitoring in colorectal cancer patients - Zakaria, Bannur; Mohd Zaki, Salleh; Hashim, Hazwanie; Tom, Hennessy; Md Nor, Azmi; MH, Zailani; Prabu, Ramasamy; ZA, Zakaria; Suneet, S; Ngow, Harris Abdullah; Henry, Guy M.; Teh, Laykek (International Journal of Pharmacy and Pharmaceutical Sciences ( IJPPS), 2014)
Objective: To provide quick and accurate clinical diagnostic tools those are currently not available leading to improper management of colorectal cancer (CRC) patients. Methods: The metabolomic profiles of 10 CRC patients treated with 5-fluorouracil and 24 healthy volunteers were analysed. The subjects were genotyped for UGT1A1*28, DPYD 1896 T>C and DPYD*5.